Cat ninja. 3, Wanted - Cody, Matthew; Cody, Matthew; Venable, Colleen A. F.; Axelrod, Jadzia; Scott, Steven (Comics author); Colleen, Marcie (Epic! originals., 2022)
"Cat Ninja: Wanted features Metro City's favorites and newcomers in tales that include a nearly cat-astrophic case of stolen identity, the not-so-villainous adventures of Master Hamster, and Adonis's first mission as one of the good guys. Enjoy six stand-alone stories, plus a five-part Cat Ninja special miniseries! "--Amazon.